Modulation of immune responses in lentiviral vector-mediated gene transfer - Annoni, Andrea; Gregori, Silvia; Naldini, Luigi; Cantore, Alessio (Cellular immunology, 2019)
•Immune responses may be detrimental to both the safety and efficacy of gene therapy.•Design and manufacturing can be tuned to reduce vector immunogenicity.•Active transgene-specific immune tolerance is desirable in gene therapy.•Novel targeted immune-modulatory strategies can be explored to improve gene therapy. Lentiviral vectors (LV) are widely used vehicles for gene transfer and therapy in pre-clinical animal models and clinical trials with promising safety and efficacy results. However, host immune responses against vector- and/or transgene-derived antigens remain a major obstacle to the success and broad applicability of gene therapy. Here we review the innate and adaptive immunological barriers to successful gene therapy, both in the context of ex vivo and in vivo LV gene therapy, mostly concerning systemic LV delivery and discuss possible means to overcome them, including vector design and production and immune modulatory strategies.